Rapid assessment of high-risk sexual behavior in street children of Tehran - Payam Roshanfekr (Shahid Beheshti University of Medical Sciences, 2020)
Introduction: Street children, due to their living and working conditions, are exposed to various injuries, and part of these are caused or exacerbated by engaging in high-risk behaviors. This study aims to determine more accurately the situation of street children's high-risk sexual behavior in Tehran in order to reduce the prevalence of AIDS. Methods: This study was conducted in 2012-13 in Tehran using rapid assessment and response (RAR) method. Data were gathered from a sample of 289 street children (boys and girls), who were selected through time-location sampling (TLS) method, and 16 interviews with key informants and 13 group discussions with street children who were selected through purposive and snowball sampling methods. Results: Children are engaged in sexual relations in two forms: forced and non-forced (mandatory or voluntarily). Among the study's sample, 8.7% reported a history of sexual abuse, and 21.1% had experienced sexual relations, in which, 37.7% of cases included sexual protection. Summary and discussion:  The present study confirms the vulnerability of street children, the negative effects of environmental factors and behavioral determinants of health and well-being, and it emphasizes the need for effective health interventions, particularly education and social support.